An Empirical Test of a Valuation Model for American Options on Futures Contracts - Shastri, Kuldeep; Tandon, Kishore (Journal of Financial and Quantitative Analysis, 1986)
Pricing models for American call and put options on futures contracts are derived herein. These models are used to investigate the efficiency of the market for options on Standard & Poor 500 and German Mark futures. The evidence presented here indicates that market prices for these options deviate substantially from their corresponding model prices. In addition, it is shown that a hedging strategy originated at prices that indicate a deviation of market from model is successful in translating the observed mispricing into excess profits after transactions costs. However, these net profits are eliminated if the origination of the strategy is delayed by one trade, or if bid-ask spreads are accounted for.